Reconstruction of Anomalous Portal Venous Branching in Right Lobe Living - Yilmaz, S; Kayaalp, C; Isik, B; Ersan, V; Otan, E; Akbulut, S; Dirican, A; Kutlu, R; Kahraman, AS; Ara, C; Yilmaz, M; Unal, B; et al. (2017)
Reconstruction of anomalous portal vein branching (APVB) during right lobe living donor liver transplantation (LDLT) can be challenging. The goal of this article is to describe our surgical technique, named the Malatya Approach, in case of APVB during right lobe LDLT. The technique unifies the APVB and obtains a funnel-shaped common extension with a circumferential fence by a saphenous vein conduit. In total, 126 (10.6%) of 1192 right lobe grafts had APVB that were divided into 2 groups according to the adopted surgical techniques: the Malatya Approach group (n=91) and the previously defined other techniques group (n=35). Both groups were compared regarding portal vein thrombosis (PVT), postoperative 90-day mortality and survival. PVT developed in 3 patients (3.3%) in the Malatya Approach group and developed in 10 (28.6%) patients for the other group (P<0.001). There were 8 (8.8%) 90-day mortalities in the Malatya Approach group (1 PVT related) and 15 patients (9 PVT related) died in the other techniques group (P<0.001). Mean follow-up time for both groups was similar (999.1 days for the Malatya Approach group versus 1024.7 days for the other group; P=0.47), but longterm survival in the Malatya Approach group was better than in the other group (84.6% versus 40%; P<0.001). Multivariate analysis revealed that the Malatya Approach group showed less PVT development and longer survival (P<0.001). This technique is promising to avoid PVT and mortalities in cases of APVB during right lobe LDLT. (C) 2017 AASLD. C1 [Yilmaz, Sezai; Kayaalp, Cuneyt; Isik, Burak; Ersan, Veysel; Otan, Emrah; Akbulut, Sami; Dirican, Abuzer; Kutlu, Ramazan; Kahraman, Aysegul Sagir; Ara, Cengiz; Yilmaz, Mehmet; Unal, Bulent; Aydin, Cemalettin; Piskin, Turgut; Ozgor, Dincer; Ates, Mustafa; Ozdemir, Fatih; Ince, Volkan; Koc, Cemalettin; Baskiran, Adil; Dogan, Sait Murat; Barut, Bora; Sumer, Fatih; Karakas, Serdar; Kutluturk, Koray; Yologlu, Saim; Gozukara, Harika] Inonu Univ, Liver Transplantat Inst, Malatya, Turkey.